DECREASED RETINAL BLOOD-FLOW IN RETINITIS-PIGMENTOSA - AKYOL, N; KUKNER, S; CELIKER, U; KOYU, H; LULECI, C (Canadian Ophthal Soc, 1995)
Objective: To determine alterations in retinal blood flow in retinitis pigmentosa (RP). Design: Case-control study. Setting: Ophthalmology department of a university-affiliated hospital in Elazig, Turkey. Subjects: Ten patients (20 eyes) with typical RP and 22 age-matched volunteer subjects (22 eyes) with no history of ocular or systemic disease. Main outcome measures: Central retinal artery peak systolic and diastolic blood flow velocity (measured by means of colour Doppler imaging), resistance index and pulsatility index. Results: The mean peak systolic and diastolic flow velocity values were significantly lower in the study group than in the control group (4.96 +/- 1.3 vs. 11.11 +/- 1.5 cm/s [p < 0.00001] and 2.15 +/- 0.4 vs. 3.40 +/- 0.9 cm/s [p < 0.0001] respectively). The mean resistance index value was significantly lower in the study group (0.55 +/- 0.05) than in the control group (0.71 +/- 0.06) (p < 0.0001), as was the mean pulsatility index value (0.94 +/- 0.18 vs. 1.45 +/- 0.36) (p < 0.00001). Conclusions: Decreased retinal blood flow is an important feature of RP.
Keywords: RETINITIS PIGMENTOSA; OCULAR HEMODYNAMICS